2005
DOI: 10.1093/nar/gni025
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility, bioinformatic analysis and power of the SAGE method to evaluate changes in transcriptome

Abstract: The serial analysis of gene expression (SAGE) method is used to study global gene expression in cells or tissues in various experimental conditions. However, its reproducibility has not yet been definitively assessed. In this study, we have evaluated the reproducibility of the SAGE method and identified the factors that affect it. The determination coefficient (R2) for the reproducibility of SAGE is 0.96. However, there are some factors that can affect the reproducibility of SAGE, such as the replication of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 27 publications
2
55
0
2
Order By: Relevance
“…Here, SAGE was used to obtain a prospective overview of cellular processes that are rapidly The proportion of tags matching with sequences in GenBank and UniGene databases reported here is consistent with other SAGE studies (11,19,20). Moreover, the reproducibility of SAGE methodology has been established previously by us (21) and by others (22). Furthermore, consistency of the differentially expressed tags identification in the four independent libraries corroborates the validity and reproducibility of SAGE results.…”
Section: Discussionsupporting
confidence: 86%
“…Here, SAGE was used to obtain a prospective overview of cellular processes that are rapidly The proportion of tags matching with sequences in GenBank and UniGene databases reported here is consistent with other SAGE studies (11,19,20). Moreover, the reproducibility of SAGE methodology has been established previously by us (21) and by others (22). Furthermore, consistency of the differentially expressed tags identification in the four independent libraries corroborates the validity and reproducibility of SAGE results.…”
Section: Discussionsupporting
confidence: 86%
“…Sequence files were analyzed using the SAGEana program, a modification of SAGEparser (St-Amand et al, Quebec, PQ, Canada;Dinel et al 2005). In brief, SAGE tags corresponding to linker sequences were discarded and replicate concatemers were counted only once.…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…We have previously shown that the SAGE method is very reproducible with r 2 Z0 . 96 between two SAGE libraries generated from two cDNA libraries constructed from the same total RNA pool (Dinel et al 2005). Classification of the transcripts was based upon the updated information of the genome directory (Adams et al 1995) found at the TIGR web site (http://www.tigr.…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…Although other techniques such as DNA microarray are limited by their ability to analyze only previously known transcripts, SAGE does not require a priori knowledge of the sequence of mRNA transcripts expressed in the tissues of interest. In addition, we recently showed (22) that the SAGE method has a very high reproducibility, with r 2 ϭ 0.96. Moreover, no mRNA species had significant difference in their level of expression estimated by two SAGE libraries constructed from the same pool of total RNA (22).…”
mentioning
confidence: 99%